PENINGKATAN KEMAMPUAN MEMBACA PUISI MENGGUNAKAN STRATEGI DIRECTED READING ACTIVITY (DRA) DI SEKOLAH DASAR - Hasmaini, Hasmaini; Sukma, Elfia; Rahmatina, Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This Class action research aims at improving students’ablities in poetriy by using the DRA srategi at class v of SDN 36 Labuhan Tanjak, Pesisir Selatan. The subjects were the teacher and 23 student of class V, the research results show some improvement. The score of teacher’s aspect increased from 71.42% un cycle I to 92.85% in cycle II. Meanwhile, the score of the students aspect also enhaced from 71.52% in cicle II. The students’ abilities also improve,first, the students’score in the pre-reading activity increased from 71.52% in cycle I to 78.52% in cycle II. Second, the students’ score the post reading activity increased from 75.65 in cycle I to 88.69% in cycle II. Thus,it can be concluded that the DRA strategy has succesfully improved the students abilities in poetry reading. Keyword : poetry Reading Ability, the DRA Strategy